Effects of exercise training on breast cancer metastasis in a rat model. Issue 1 (February 2017) - Alvarado, Antonieta; Gil da Costa, Rui M.; Faustino‐Rocha, Ana I.; Ferreira, Rita; Lopes, Carlos; Oliveira, Paula A.; Colaço, Bruno
Summary: Exercise training is thought to play a protective role against cancer development and metastasis, either by reducing hormonal stimulation of hormone‐dependent cancers or by reducing the permeability of vascular walls towards invading metastatic cells. The purpose of this work was to evaluate the role of long‐term exercise training in the development and metastasis of breast cancer, in an immune‐competent 1‐methyl‐1‐nitrosourea (MNU) induced rat model. A single MNU dose was administered to Sprague‐Dawley rats at 50 days of age and the rats were subjected to exercise training on a treadmill at 20 m/min, 60 min/day, 5 days/week for 35 weeks. Exercised animals developed slightly less (2.30 ± 1.42) tumours per animal than sedentary animals (2.55 ± 1.44) and did not develop any metastasis, while two pulmonary metastases were observed in the sedentary group. All primary neoplasms and their metastases were positive for oestrogen (ER) α and progesterone (PR) receptors, indicating high hormonal sensitivity. Interestingly, exercise training increased circulating oestrogen levels, thus suggesting that the mechanism might involve either or both of a protective hormone‐independent effect and modulation of tumoural vascularization.